The car just a Web browser with tires. - Bretz, E.A.
Automakers are working at equipping vehicles with not only Internet access but also such services as on-demand emergency assistance, navigation, and traffic reports. To provide access to these services and the hardware needed to deliver them, software developers and automotive electronics engineers are collaborating on voice recognition and speech synthesis interfaces. Everyone agrees, it seems, that by using speech to control equipment, distractions will be minimal and drivers can keep their hands and eyes devoted to the wheel and the road. For rear seat passengers, where distraction is a plus if it prevents the plaintive ?Are we there yet?,? automobile manufacturers aim to supply Internet access, and entertainment delivered by DVD, CD-ROM, or the Internet, depending on quality desired for whatever content is delivered. Most major vehicle manufacturers worldwide agree that the vehicle will be connected to the Internet. Popular demand is the key. One ultimate application is all it will really take for consumers to insist on Internet connectivity in their cars
Keywords: CD-ROM.; DVD; Internet access; Internet connectivity; Automotive electronics engineers; Car makers; Entertainment; On-demand emergency assistance; On-demand navigation; Speech synthesis interfaces; Traffic reports; Voice recognition interfaces